Research on Internet hotspot information detection - ZENG Yi-ling1; XU Hong-bo1 (Tongxin xuebao)
To recognize the hotspot information through great deal of Internet data,the hotspot information detection al-gorithm（HID） was designed.Based on segmented word joint,with a customized noise library and multi-level filtering strategies,HID was provided with the ability to detect hotspot information in large amount of Internet pages.Experiment on TDT international standard test corpus proved the efficiency of HID.